Post a New Question

Algebra

posted by .

I can not get he correct answer -10.

-3/3{a+c(b+5)-(-6+a)}
a=1, b=-6, c=-4

  • Algebra -

    starting with
    -3/3{a+c(b+5)-(-6+a)}
    = -3/3{1+(-4)((-6)+5)-(-6+1)}
    let's work our way from the inside out:
    -3/3{1+(-4)(-6+5)-(-6+1)}
    -3/3{1+(-4)(-1)-(-5)}
    -3/3{1+4+5)}
    -3/3{10}
    -1(10)
    -10

    Note that the division is done first, then the multiplication, left-to-right

Answer This Question

First Name
School Subject
Your Answer

Related Questions

More Related Questions

Post a New Question